2012
DOI: 10.1103/physrevlett.109.221102
|View full text |Cite
|
Sign up to set email alerts
|

Binary Black-Hole Mergers in Magnetized Disks: Simulations in Full General Relativity

Abstract: We present results from the first fully general relativistic, magnetohydrodynamic (GRMHD) simulations of an equal-mass black hole binary (BHBH) in a magnetized, circumbinary accretion disk. We simulate both the pre and post-decoupling phases of a BHBH-disk system and both "cooling" and "no-cooling" gas flows. Prior to decoupling, the competition between the binary tidal torques and the effective viscous torques due to MHD turbulence depletes the disk interior to the binary orbit. However, it also induces a two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
174
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(184 citation statements)
references
References 45 publications
8
174
1
1
Order By: Relevance
“…This is done in order to avoid failures during the conversion from conserved to primitive variables (see [28] for details). In order to preserve the divergence-free character of the magnetic field, we evolve directly the vector potential using the modified Lorenz gauge [32,33]. This guarantees divergence-free magnetic fields and avoids spurious magnetic field amplifications at the boundary between refinement levels.…”
Section: Methodsmentioning
confidence: 99%
“…This is done in order to avoid failures during the conversion from conserved to primitive variables (see [28] for details). In order to preserve the divergence-free character of the magnetic field, we evolve directly the vector potential using the modified Lorenz gauge [32,33]. This guarantees divergence-free magnetic fields and avoids spurious magnetic field amplifications at the boundary between refinement levels.…”
Section: Methodsmentioning
confidence: 99%
“…Initial work focused on matter accreting directly from a circumbinary disk to the BHs during the few binary orbits immediately preceding merger. These investigations were "proof of principle" calculations, designed to show that gas dynamics and full solution of the Einstein Field Equations could be done in tandem (Bode et al 2010;Palenzuela et al 2010;Farris et al 2011;Bode et al 2012;Farris et al 2012;Giacomazzo et al 2012;Gold et al 2014). However, because of their brief duration, the total mass transferred from the circumbinary disk to the central cavity was relatively small and no formation of individual disks around the BHs was observed.…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that these torques prevented accretion onto the black holes. However, multidimensional numerical simulations (MacFadyen & Milosavljević 2008;Noble et al 2012;Farris et al 2012;D'Orazio et al 2013;Gold et al 2014;Farris et al 2014Farris et al , 2015bBankert et al 2015;Schnittman & Krolik 2015;del Valle & Escala 2015;Young & Clarke 2015;D'Orazio et al 2016;Muñoz & Lai 2016;Miranda et al 2017) have demonstrated that gas streams enter the circumbinary cavity and feed accretion disks around each of the individual black holes. We term these disks "minidisks."…”
Section: Introductionmentioning
confidence: 99%